1993
DOI: 10.1099/00207713-43-2-266
|View full text |Cite
|
Sign up to set email alerts
|

A New Actinomycete Species, Nocardiopsis lucentensis sp. nov.

Abstract: A new species of the genus Nocardiopsis, for which we propose the name Nocardiopsis lucentensis sp. nov. (type strain, strain DSM 44048), was isolated from a salt marsh soil sample near Alicante, Spain. Whole-cell hydrolysates contain the meso isomer of diaminopimelic acid and no characteristic sugar; thus, the cell wall composition is type 111. Menaquinone MK-lO(H,) is the major menaquinone, and the phospholipid type is type PI11 (phosphatidylcholine present). Spore chains are rectiflexibilis, and in the earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 32 publications
1
60
1
Order By: Relevance
“…Grund and Kroppenstedt (10) found that Nocardiopsis dassonvillei and the two subspecies of Nocardiopsis alba have the same menaquinone composition. A different menaquinone composition was found for Nocardiopsis alborubida and Nocardiopsis listen (lo), while a third type was reported for Nocardiopsis lucentensis (27). This apparent lack of congruence provides another example of the difficulties involved in comparing the evolution of menaquinones (9).…”
Section: Taccgcggc[t/g]gctg3') 536f (5'cagc[c/a]gccgcggtaat[t/a]cmentioning
confidence: 99%
See 1 more Smart Citation
“…Grund and Kroppenstedt (10) found that Nocardiopsis dassonvillei and the two subspecies of Nocardiopsis alba have the same menaquinone composition. A different menaquinone composition was found for Nocardiopsis alborubida and Nocardiopsis listen (lo), while a third type was reported for Nocardiopsis lucentensis (27). This apparent lack of congruence provides another example of the difficulties involved in comparing the evolution of menaquinones (9).…”
Section: Taccgcggc[t/g]gctg3') 536f (5'cagc[c/a]gccgcggtaat[t/a]cmentioning
confidence: 99%
“…To date, a comprehensive DNA-DNA hybridization study of all Nocardiopsis species has not been carried out. However, the limited DNA-DNA hybridization data presented in the description of Nocardiopsis lucentensis (27) could be compared with the 16s rDNA sequence analysis data. These DNA-DNA hybridization data demonstrated that Nocardiopsis lucentensis is a true species when this organism was compared with Nocardiopsis dassonvillei, Nocardiopsis alborubida, Nocardiopsis listen', Nocardiopsis alba subsp.…”
Section: Taccgcggc[t/g]gctg3') 536f (5'cagc[c/a]gccgcggtaat[t/a]cmentioning
confidence: 99%
“…At the time of writing, the taxon encompasses 28 recognized species and 4 subspecies, which form a distinct clade within the evolutionary radiation occupied by members of the family Nocardiopsaceae (Rainey et al, 1996). Nocardiopsis strains are frequently isolated from saline soils (Yassin et al, 1993a;Li et al, , 2006, but they have also been recovered from an alkaline slag dump (Schippers et al, 2002), indoor environments (Peltola et al, 2001), the atmosphere of a composting facility (Kämpfer et al, 2002) and clinical material (Bernatchez & Lebreux, 1991;Yassin et al, 1997). In the present polyphasic study, an actinomycete isolated from household waste was shown to represent a novel species of the genus Nocardiopsis.…”
mentioning
confidence: 99%
“…alba, Nocardiopsis alba subsp. prasina and Nocardiopsis synnemataformans (Meyer, 1976 ;Grund & Kroppenstedt, 1990 ;Abyzov et al, 1983 ;Yassin et al, 1993Yassin et al, , 1997Al-Tai & Ruan, 1994 ;Miyashita et al, 1984). The subspecies N. alba subsp.…”
Section: Introductionmentioning
confidence: 99%